2011
DOI: 10.1165/rcmb.2009-0467oc
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminus of Heat Shock Protein 70–Interacting Protein–Dependent GTP Cyclohydrolase I Degradation in Lambs with Increased Pulmonary Blood Flow

Abstract: We showed that nitric oxide (NO) signaling is decreased in the pulmonary vasculature before the development of endothelial dysfunction in a lamb model of congenital heart disease and increased pulmonary blood flow (Shunt). The elucidation of the molecular mechanism by which this occurs was the purpose of this study. Here, we demonstrate that concentrations of the endogenous NO synthase (NOS) inhibitor, asymmetric dimethylarginine (ADMA), are elevated, whereas the NOS cofactor tetrahydrobiopterin (BH(4)) is dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…Our previous studies have demonstrated that in Shunt lambs, ADMA levels are increased due to a reduction in DDAH activity (47). Interestingly, this reduction in DDAH activity does not correlate with a reduction in either DDAH1- (Fig.…”
Section: L-arginine Supplementation Prevents the Mitochondrial Redistmentioning
confidence: 80%
See 2 more Smart Citations
“…Our previous studies have demonstrated that in Shunt lambs, ADMA levels are increased due to a reduction in DDAH activity (47). Interestingly, this reduction in DDAH activity does not correlate with a reduction in either DDAH1- (Fig.…”
Section: L-arginine Supplementation Prevents the Mitochondrial Redistmentioning
confidence: 80%
“…The interactions of eNOS/Hsp90 or nitrated CrAT levels were analyzed by immunoprecipitation (IP) analysis as described (47). The efficiency of each IP was normalized by reprobing the membranes with the IP antibody (IP:Hsp90) or by Western blot analysis of 30 lg of the IP protein extract probed using a specific antibody for CrAT (IP:3-nitrotyrosine ).…”
Section: Immunoprecipitation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…NO and superoxide generation was monitored under conditions that stimulate maximal velocity of the enzyme [28]. The S1177D mutant generates significantly more NO than wildtype eNOS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that this sequence could interact with the positively charged eNOS mitochondrial translocation loop located at aa 627-631 (RRKRK) (14). Furthermore, we have recently shown in an animal model of pulmonary hypertension associated with increased pulmonary blood flow that increases in ADMA correlates with increased activities of CHIP and Hsp70 (47) and increased translocation of eNOS to the mitochondrion (48). However, further studies will be required to determine whether Hsp70 and/or CHIP play a role in regulating eNOS translocation to the mitochondrion.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%